Analysis of Two Complementary Single-Gene Deletion Mutant Libraries of Salmonella Typhimurium in Intraperitoneal Infection of BALB/c Mice - Silva-Valenzuela, Cecilia A.; Molina-Quiroz, Roberto C.; Desai, Prerak; Valenzuela, Camila; Porwollik, Steffen; Zhao, Ming; Hoffman, Robert M.; Andrews-Polymenis, Helene; Contreras, Inés; Santiviago, Carlos A.; McClelland, Michael (Frontiers in Microbiology, 2016)
Two pools of individual single gene deletion (SGD) mutants of S. Typhimurium 14028s encompassing deletions of 3,923 annotated non-essential ORFs and sRNAs were screened by intraperitoneal (IP) injection in BALB/c mice followed by recovery from spleen and liver two days post infection. The relative abundance of each mutant was measured by microarray hybridization. The two mutant libraries differed in the orientation of the antibiotic resistance cassettes (either sense-oriented KanR, SGD-K, or antisense-oriented CmR, SGD-C). Consistent systemic colonization defects were observed in both libraries and both organs for hundreds of mutants of genes previously reported to be important after IP injection in this animal model, and for about 100 new candidate genes required for systemic colonization. Four mutants with a range of apparent fitness defects were confirmed using competitive infections with the wild-type parental strain: ΔSTM0286, ΔSTM0551, ΔSTM2363 and ΔSTM3356. Two mutants, ΔSTM0286 and ΔSTM2363, were then complemented in trans with a plasmid encoding an intact copy of the corresponding wild-type gene, and regained the ability to fully colonize BALB/c mice systemically. These results suggest the presence of many more undiscovered Salmonella genes with phenotypes in IP infection of BALB/c mice, and validate the libraries for application to other systems.